2010
DOI: 10.1038/ni.1867
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor PU.1 is required for the development of IL-9-producing T cells and allergic inflammation

Abstract: CD4+ T helper cells acquire effector phenotypes that promote specialized inflammatory responses. We show that the ETS family transcription factor, PU.1 was required for the development of an interleukin 9 (IL-9)-secreting subset of TH cells. Decreasing PU.1 expression either by conditional deletion in murine T cells or siRNA in human T cells impaired IL-9 production, while ectopic PU.1 expression promoted IL-9 production. Mice with PU.1-deficient T cells developed normal TH2 responses in vivo, but exhibited at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
609
3
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(641 citation statements)
references
References 45 publications
21
609
3
8
Order By: Relevance
“…PU.1 est essentiel pour la différenciation des cellules Th9 [8]. Il interagit avec le promoteur de l'Il9 et est également responsable du recrutement d'histone acétyle transférases (HAT) qui facilitent l'accessibilité à la chromatine [7,8]. En son absence, la capacité des lymphocytes T à produire de l'IL-9 est diminuée et est associée, simultanément, à une augmentation de production des cytokines de type Th2 [7].…”
Section: Les Cytokines Exprimées Par Les Lymphocytes Th9unclassified
See 2 more Smart Citations
“…PU.1 est essentiel pour la différenciation des cellules Th9 [8]. Il interagit avec le promoteur de l'Il9 et est également responsable du recrutement d'histone acétyle transférases (HAT) qui facilitent l'accessibilité à la chromatine [7,8]. En son absence, la capacité des lymphocytes T à produire de l'IL-9 est diminuée et est associée, simultanément, à une augmentation de production des cytokines de type Th2 [7].…”
Section: Les Cytokines Exprimées Par Les Lymphocytes Th9unclassified
“…Il interagit avec le promoteur de l'Il9 et est également responsable du recrutement d'histone acétyle transférases (HAT) qui facilitent l'accessibilité à la chromatine [7,8]. En son absence, la capacité des lymphocytes T à produire de l'IL-9 est diminuée et est associée, simultanément, à une augmentation de production des cytokines de type Th2 [7]. À noter enfin, que l'activation des lymphocytes naïfs par l'intermé-diaire des récepteurs GITR (glucocorticoid-induced tumor necrosis factor receptor [TNFR] related protein) favorise la différenciation Th9 par une voie de signalisation impliquant TRAF6 (TNF-receptor associated factor 6) et NFκB (nuclear factor-kappa B) et que des anticorps …”
Section: Les Cytokines Exprimées Par Les Lymphocytes Th9unclassified
See 1 more Smart Citation
“…[6][7][8][9][10][11] In T-cell differentiation, for example, an obligatory drop in PU.1 activity is concomitantly balanced by a surge in the Ets-1 activity, [11][12][13] and both are differentially required in the peripheral Th subsets. [14][15][16] Aberrant activity in either paralog is linked to a spectrum of diseases including rheumatism, 17 cancer [18][19][20][21] and Alzheimer disease. [22][23][24] Functional heterogeneity occurs even among very close ETS sequence homologs, as in the case of PU.1 and Spi-B, wherein Spi-B cannot compensate for the absence of PU.1-mediated B-cell signaling in PU.1-null mice.…”
Section: Introductionmentioning
confidence: 99%
“…PU.1 is reported to be an important transcriptional regulator of Th9 cell differentiation (14). In addition, a few studies indicated that other factors, such as NF-kB, NFATc2, and IFN regulatory factor 4 (IRF-4), regulate IL-9 production in Th9 cells (15)(16)(17).…”
mentioning
confidence: 99%